一种证券算法交易过程中的实时算法交易总线系统 (2021)
本发明公开了一种证券算法交易过程中的实时算法交易总线系统，系统包括证券算法交易数据处理接口模块、证券交易数据算法总线模块，证券算法交易数据处理接口模块分别与证券交易数据算法总线模块信连接等；本发明具有规范稳定的算法投资交易接口，丰富的算法投资交易功能，可以快速、稳定地对接扩展更多的三方算法，可全方位满足大部分机构客户的交易执行需求，可帮助机构和高端个人投资者显著降低冲击成本，减少异常交易的发生，能够帮助券商快速搭建起自身的投资交易系统，可以连接深圳、上海实时行情或者轻量行情，快速接入券商柜台系统，解决了现有国内各投资交易系统供应商的技术壁垒之下难以形成能够适应多环境，部署不够灵活的问题。 The invention discloses a real-time algorithm transaction bus system in a securities algorithm transaction process. The system comprises a securities algorithm transaction data processing interface module and a securities transaction data algorithm bus module, and the securities algorithm transaction data processing interface module is in communication connection with the securities transaction data algorithm bus module. The invention has a normative and stable algorithm investment transaction interface and rich algorithm investment transaction functions, can quickly and stably butt and expandmore three-party algorithms, can comprehensively meet transaction execution requirements of most institution customers, can he